The role of Erasmus+ in the internationalization of higher education - Kabanbayeva, Gulbakyt (KAZGUU University, Nazarbayev University, 2018)
This article shows how, within the framework of the Erasmus + project, structural work is being done on the internationalization of higher education, as one of the objectives of the project. The aim of the project is to expand the cooperation of business universities in partner countries by changing the education paradigm in accordance with the requirements of the Bologna Process. Improvement of such cooperation will lead to a gradual increase in the effectiveness of the national development strategy, priority implementation, as well as changes in the situation in the field of entrepreneurship and employment of graduates. The starting point of the project is to study and determine the current professional structure necessary for modern employers in partner countries. This study will create an understanding of problem areas in legislation, education and business standards and will form part of the basis for their further correction. After determining the current experience of cooperation with business and universities, as well as the requirements of the business environment, the project is aimed at drawing up and implementing a new standard for establishing links between companies and universities, whether for launching innovative products or targeted future training of personnel or sharing experiences with young entrepreneurs. It is also expected that such a standard will also implement some practice-oriented training programs, tools and methods in a form suitable for implementation in the learning process.
Keywords: educational process; Higher Education; new social environment; universities and business; education system education system